2011
DOI: 10.1002/hed.21436
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of bilateral cervical metastases in oropharyngeal squamous cell carcinoma: A retrospective analysis of 352 cases after bilateral neck dissection

Abstract: Bilateral neck dissection should be recommended for all but T1 and selected cases of T2 carcinomas of the tonsillar fossa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
6

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 17 publications
0
41
0
6
Order By: Relevance
“…Researchers [7][8]33] have suggested that patients with primary tumor of the floor of the mouth, which is known to have a rich and bilateral lymphatic drainage pattern exhibit a higher risk of contralateral metastases than those with tongue tumors or those invading the retromolar trigone. It was also found that a higher rate of contralateral metastases in the base of the tongue, even in early tumors, than in tumors of the tonsillar fossa or the body and the tip of the tongue by Olzowy et al [21] and Califano et al [34]. However, diverse findings have also been reported the most-contrasting data showing a higher incidence of CLNM in cases of lower gum carcinoma (25%) in comparison with those tumors starting on the mobile tongue (15.4%) [13].…”
Section: Tumor Locationmentioning
confidence: 92%
See 4 more Smart Citations
“…Researchers [7][8]33] have suggested that patients with primary tumor of the floor of the mouth, which is known to have a rich and bilateral lymphatic drainage pattern exhibit a higher risk of contralateral metastases than those with tongue tumors or those invading the retromolar trigone. It was also found that a higher rate of contralateral metastases in the base of the tongue, even in early tumors, than in tumors of the tonsillar fossa or the body and the tip of the tongue by Olzowy et al [21] and Califano et al [34]. However, diverse findings have also been reported the most-contrasting data showing a higher incidence of CLNM in cases of lower gum carcinoma (25%) in comparison with those tumors starting on the mobile tongue (15.4%) [13].…”
Section: Tumor Locationmentioning
confidence: 92%
“…Other authors [13,21] have further demonstrated that patients with multiple ipsilateral positive nodes (two or more) presented with a higher risk for contralateral metastases or bilateral metastases than those with a single positive node or negative nodes.…”
Section: Parameters Of the Cervical (Regional) Lymph Nodesmentioning
confidence: 92%
See 3 more Smart Citations